Występowanie rysia eurazjatyckiego ( Lynx lynx ) w Puszczy Augustowskiej : Occurrence of Eurasian lynx ( Lynx lynx ) in Augustów Forest - Harmuszkiewicz, Joanna (Polskie Towarzystwo Leśne, 2011)
Snow tracking of the Eurasian lynx was conducted in the Augustowska Forest during 2008/2009 winter. The tracking results and year−long monitoring of the predators showed the presence of 19 to 20 lynx individuals in the territory of the Augustowska Forest. Significant differences were found in the size of the territories occupied by adult males and adult females. Areas occupied by females carrying kittens were separated from each other, but partially overlapped with areas of male cats. The density of predators was low (1.67−1.75 individuals/100 km), which may be because of the simplified structure of the forest environment and low density of ungulate mammals constituting the basic food of the lynx. : Sylwan 155 (8): 572-578